Valuing Whiteness: The Presumed Innocence of Musical Truth - Johnson-Williams, Erin (Current Musicology, 2023)
The end of 2020 presents a crucial time to reflect on the challenges that lie ahead for decolonizing and disrupting musicology. While many have flocked to what I call here the “presumed innocence of musical truth” during the time of Covid-19, any move to disaggregate music from political realities—both the contexts within which it was first created, and those that have upheld the musical traditions that are now in place—carries the risk of perpetuating the destructive possibility that loving the canon can also be our alibi for (or, as I propose here, our “claim to innocence” about) why the discipline of musicology has been so slow to engage with antiracist and decolonial debates in a sustained way. Thinking critically about systemic racism at the end of a particularly challenging year, the time is ripe for interrogating how the institutional structures that uphold western art music are still tied to values about aesthetic truths that have yet to be decolonized. In this article I respond to critical race and Indigenous studies theorists Eve Tuck and K. Wayne Yang in their renowned 2012 article “Decolonization is not a Metaphor,” by outlining three “moves to innocence” that are prevalent in music academia, followed by a proposed “move to disruption” about musical value that contributes to an actively “decolonizing” musicology. Focusing on the themes of truth and value, I argue that the next decade holds an opportunity to engage with the ideas that might productively disrupt our discipline the most.